The Oxford handbook of the new private law - Gold, Andrew S. 1973-; Goldberg, John C. P. 1961-; Kelly, Daniel B. ca. 20./21. Jh; Sherwin, Emily 1955-; Smith, Henry E. 1965- (Oxford University Press, 2021)
This volume promises to help redefine and reinvigorate the subject of private law, a domain that includes property, contract, and tort law, as well as intellectual property, unjust enrichment, and equity. It emphasizes cross-cutting perspectives and relations between areas of private law, with special attention to the doctrines and structures of the law - an approach now known as 'the New Private Law.'
Also issued in print: 2020. - Includes bibliographical references and index
Internal and External Perspectives: On the New Private Law Methodology - Andrew S. Gold -- - Private Law and Local Custom - Nathan B. Oman -- - Autonomy and Pluralism in Private Law - Hanoch Dagan -- - A Feminist Perspective: Private Law as Unjust Enrichment - Anita Bernstein -- - Historical Perspectives - Joshua Getzler -- - Civil and Common Law - Lionel Smith -- - Function and Form in Contract Law - Alan Schwartz, Daniel Markovits -- - Torts - John C. P. Goldberg -- - Property - J. E. Penner -- - Unjust Enrichment and Restitution - Andrew Burrows -- - Trust Law: Private Ordering and the Branching of American Trust Law - John D. Morley, Robert H. Sitkoff -- - Natural Rights and Natural Law - Dennis Klimchuk -- - Corporate Law - Paul B. Miller -- - The Employment Relationship as an Object of Employment Law - Aditi Bagchi -- - New Private Law and the Family - Margaret F. Brinig -- - The New Private Law and Intellectual Property: Calibrating Copyright on the Common Law Continuum - Molly Shaffer Van Houweling -- - Traditional Knowledge and Private Law - Ruth L. Okediji -- - Insurance - Kenneth S. Abraham -- - Formalism and Realism in Private Law - Emily Sherwin -- - Privity - Mark P. Gergen -- - Good Faith in Contractual Exchanges - Richard R.W. Brooks -- - Corrective Justice: Sovereign or Subordinate? - Gregory C. Keating -- - The Rule of Law - Lisa M. Austin -- - Defenses - Robert Stevens -- - Equity - Ben McFarlane -- - Remedies - Samuel L. Bray -- - Private and Public Law - Thomas W. Merrill -- - Fiduciary Law - W. Bradley Wendel -- - False Advertising Law - Gregory Klass -- - Civil Recourse Theory - Benjamin C. Zipursky -- - Kantian Perspectives on Private Law - Arthur Ripstein -- - Law and Economics - Daniel B. Kelly -- - New Institutional Economics - Barak Richman -- - Psychology and the New Private Law - Tess Wilkinson-Ryan -- - Systems Theory: Emergent Private Law - Henry E. Smit
Keywords: Civil law; Natural law; Law and economics; Trusts and trustees